Conceptual framework of Digital Health Public Emergency System: digital twins and multiparadigm simulation - Rodríguez Aguilar, Román; Marmolejo Saucedo, José Antonio (My University, 2020)
Introduction: Two major technological paradigms have been developed in recent years, digital twins and the multiparadigm simulation. In the Health Sector, the enormous potential of both approaches for the management of public health emergencies is envisioned. Objectives: This study aims to develop the conceptual framework for the development of a Digital Public Health Emergency System. Methods: The integration of the digital twins in health with the multi-paradigm simulation for the design of a digital system of public health emergencies is proposed.
Keywords: Digital twin; Multiparadigm simulation; Hybrid simulation; Health public; Pervasive health